PHYSIOLOGICAL QUALITY OF SEEDS OF BEANS SUBMITTED THE WASTEWATER IN A LABORATORY - de Souza, J. M.; da Silva, L. D.; Pereira, L. R.; dos Reis, E. F.; Garcia, G. de O. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The objective was to evaluate the influence of wastewater on the germination and vigor of bean seeds cv. Serrano in laboratory. The experimental design was completely randomized with four replications of 25 seeds and six treatments: seeds without soaking, seeds soaked in water for 1 h, seeds soaked in swine wastewater for 1 and 2 h, seeds soaked in cheese wastewater whey (10%) for 1 to 2 h. Were evaluated: biometrics seeds, germination, first count, germination speed index, average time and relative frequency of germination, length of root and shoot, fresh weight and dry shoot and root. The whey water (10%) and pig farming provided an improvement in germination speed index. The whey water (10%) provided greater root length, and shoot and fresh weight of the root when used for 1 and 2 h, respectively. The wastewater did not affect the physiological quality of seeds, making alternatives for reuse in bean seed germination cv. Serrano.